Burns unit at the Hospital de Clínicas of the Universidade Federal de Uberlândia, Brazil: an epidemiological study - Iván Orlando Gonzales Mego; Sinval Soares Cruvinel; Antonio Ricardo Duarte; Gilberto Andre Teles-de-Oliveira-Junior; Raissa Martins da Silva Carneiro (Revista Brasileira de Cirurgia Plástica)
Introduction: Burns, a public health problem, are injuries that can occur on the skin or other tissues of the body resulting from the trauma of thermal origin, which can cause mild, severe injuries and even death. Thus, the epidemiological characteristics of patients seen at the Burn unit of the Hospital de Clínicas of the Universidade Federal de Uberlândia are studied. Methods: Cross-sectional study of the data recorded in patients’ medical records treated for the burn at the Burn Units from 2016 to 2019. Results: 252 medical records were reviewed, with the male gender of the adult group being most affected. The main causal agent was the flammable liquid (42.4%) with a predominance of alcohol (66.35), occurring at home (59.9%). The average percentage of burned body surface was 17.7%, requiring a graft or surgical debridement in 25% of the patients. The average hospital stay was 23.3 days, requiring 8.7% of the Intensive Care Unit. The attempt at selfextermination was 5.5%, with a general death rate of 3.5%. Conclusions: Burn patients treated at the Burn Unit of the Hospital de Clínicas of the Universidade Federal de Uberlândia encompasses more of the young and adult population, with alcohol being the predominant cause, with an average death rate like other regions. This study will help create measures in search of reducing the number of cases and adapting the care quantitatively and qualitatively, contributing to the elaboration of care protocols to ensure the quality of the care of the patients and the population.